2017
DOI: 10.1021/acs.joc.7b00282
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dipolar Cycloaddition Reactions of Low-Valent Rhodium and Iridium Complexes with Arylnitrile N-Oxides

Abstract: The reactions between low-valent Rh(I) and Ir(I) metal–carbonyl complexes and arylnitrile oxides possess the electronic and structural features of 1,3-dipolar cycloadditions. Density functional theory (DFT) calculations on these reactions, involving both cyclopentadienyl and carboranyl ligands on the metal carbonyl, explain the ease of the chemical processes and the stabilities of the resulting metallaisoxazolin-5-ones. The metal–carbonyl bond has partial double bond character according to the Wiberg index cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Hence these reactions are better described as inverse‐electron‐demand 1,3‐dipolar cycloadditions. Similar 1,3‐dipolar cycloaddition involving metal carbene species has been reported previously, [ 25 ] in which the 1,3‐dipole, nitrile oxide, also plays the role of electrophile and prefers to react with electron‐rich metal carbenes. It is worth noting that a very recent work of Zhu and coworkers also attempt to address a similar issue on the regioselectivity of the reaction shown in eqn 3 from an aromaticity perspective.…”
Section: Discussionsupporting
confidence: 82%
“…Hence these reactions are better described as inverse‐electron‐demand 1,3‐dipolar cycloadditions. Similar 1,3‐dipolar cycloaddition involving metal carbene species has been reported previously, [ 25 ] in which the 1,3‐dipole, nitrile oxide, also plays the role of electrophile and prefers to react with electron‐rich metal carbenes. It is worth noting that a very recent work of Zhu and coworkers also attempt to address a similar issue on the regioselectivity of the reaction shown in eqn 3 from an aromaticity perspective.…”
Section: Discussionsupporting
confidence: 82%
“…With the development of computational methodologies, in the last few decades, the growing interest of organic chemists for their application in the study of 1,3-dipolar cycloaddition reactions has been demonstrated by the increasing number of publications in this area [11][12][13][14][15][16].…”
Section: 3-dipolar Cycloadditionmentioning
confidence: 99%
“…In this review, we are going to show the recent applications (2018-2023) of DFT methods to mechanistic speculation on reaction routes of 1,3-CDs classified on the basis of the different involved dipoles, i.e., 1,3-dipoles of propargyl/allenyl type (aza-ylides and nitrile oxides) and allyl type (azomethine ylides and nitrones) that appeared in the literature in the last few years. With the development of computational methodologies, in the last few decades, the growing interest of organic chemists for their application in the study of 1,3-dipolar cycloaddition reactions has been demonstrated by the increasing number of publications in this area [11][12][13][14][15][16].…”
Section: 3-dipolar Cycloadditionmentioning
confidence: 99%
“…On the other hand, first-row cobalt analogue 1f decomposes almost immediately in solution at room temperature (Table , entry 6). , The ligands attached to the metal also influence the stability of the complex: Ir complex with PPh 3 (Table , entry 4) is significantly more stable than those with CO (Table , entries 1–3). These observations agree with recent theoretical studies on the synthesis of these metallacycles …”
Section: Introductionmentioning
confidence: 99%
“…These observations agree with recent theoretical studies on the synthesis of these metallacycles. 10 We have now investigated the mechanism of the thermal decarboxylation of the metallaisoxazolin-5-ones using density functional theory (DFT) methods and report the factors influencing the reaction rates and products.…”
Section: ■ Introductionmentioning
confidence: 99%